C-type natriuretic peptide stimulates chicken myoblast differentiation through NPRB/NPRC receptors and metabolism pathway - Hua-yun HUANG; Zhong LIANG; Long-zhou LIU; Chun-miao LI; Zhen-yang HUANG; Qian-bao WANG; Shou-feng LI; Zhen-hua ZHAO (Journal of Integrative Agriculture)
Skeletal muscle development is closely related with the amount of meat production and its quality in chickens. Natriuretic peptides (NPs) play an important role in myotube formation and fat oxidation of skeletal muscle in animals. The effect of C-type natriuretic peptide (CNP), an important member of the NPs, and its underlying molecular mechanisms in skeletal muscle are incompletely understood. Treatment of myoblasts with CNP led to enhanced proliferation/differentiation and significantly upregulated (P<0.05) mRNA expression of the CNP receptors natriuretic peptide receptor B (NPRB) and the clearance receptor C (NPRC). In cells exposed to CNP, 142 differentially expressed genes (84 up-regulation and 58 down-regulation) (P<0.05) were identified by RNA-sequencing compared with those in control cells. Sixteen genes were significantly enriched (P<0.05) in the metabolic pathway, and six of them (phospholipase C β4, phospholipase C β2, phosphoglycerate mutase 1, creatine kinase B, peroxiredoxin 6 and CD38) were closely related to skeletal muscle development and differentially expressed. In conclusion, CNP stimulated differentiation of myoblasts by upregulating expression of the NPRB and NPRC receptors and enriching key genes in the metabolic pathway.